Atypical reward anticipation in impulsive individuals: evidence from EEG and experiential delay discounting - Zakirov, Felix; Sysoeva, Olga (Frontiers in Psychology, 2026)
BackgroundImpulsivity is characterized by impaired inhibition of thoughts and actions and a reduced ability to weigh the consequences of behavior. Importantly, impulsivity has been associated with altered reward processing and reward anticipation.MethodsWe aimed to investigate neurophysiological indices of impulsive behavior using an experiential delay discounting task with 64-channel EEG in neurotypical adults (n = 54). Impulsive behavior was operationalized as the preference for smaller, immediate rewards over larger, delayed rewards with the delay varied from 1 to 30 s in different blocks.ResultsWe registered feedback-related fronto-central theta and centro-parietal delta power, although did not find any correlation between impulsive behavior and these neurophysiological measures of reward sensitivity. However, we found higher power spectral density in the alpha band over parieto-occipital region during reward anticipation in individuals exhibiting more impulsive behavior in our task.ConclusionThese results suggest that impulsive individuals have less efficient mechanisms of reward anticipation, potentially resulting in lower tolerance for waiting.